Preliminary Insights Into The Benefits Qur’an Memorisation Learning In Early Childhood Education - WULANDARI, RETNO (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Indonesia has a population with the majority embracing Islam. Indonesian people hold the Islamic religion not only as a belief or culture that must be followed and adhered to. Therefore, there are many Islamic-based schools in Indonesia, including Islamic-based preschools. Tahfidz Qur'an is one of the Islamic-based learning programs in kindergarten. For this reason, this article aims to see what benefits there are from the Tahfidz Qur'an program for preschool. This research is qualitative research with the type of library study. Data obtained from collecting references in the form of scientific articles, books and previous research. Data analysis techniques are carried out by selecting, comparing, combining and sorting so that relevant ones are found. As a result, the Al-Qur'an memorization program in early childhood education has a positive impact on aspects of early childhood development, especially on aspects of cognitive, language and social emotional development. Even so, the tahfidz Qur'an program for children must be provided through fun activities such as through play activities, or by using media that is attractive to young children. This is done so that children do not feel pressured by the memorization targets set by the school.